Pengaruh Pengelolaan Dana Bantuan Operasional Sekolah Terhadap Sarana dan Prasarana Pembelajaran Ips Terpadu di SMP Negeri 1 Tilango Kabupaten Gorontalo - Harson Lamusu; Radia Hafid; Agil Bahsoan; Usman Moonti; Melizubaida Mahmud (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The research aims to determine to what extent the impact of BOS Fund Management on Integrated Social Science Learning Facilities and Infrastructure at SMP Negeri 1 Tilango, Gorontalo Regency. The research method used in the research is quantitative, where the data are collected through observation, interview, questionnaire, and documentation. The research populations are the entire school community for 344 people whereas its samples are 44 people. The method of analysis employs simple regression analysis. The results of the correlations analysis indicate that there is a strong relationship between the Management Of School Operational Assistance (BOS) Fund On Integrated Social Science Learning Facilities and Infrastructure at SMP Negeri 1 Tilango, Gorontalo Regency, with a correlations coefficient value of 0,526. In addition, the calculations of coefficient of determination shows R square for 0.277, which means that 27.7% of the variability regarding integrated Social Science Learning Facilities and Infrastructure at SMP Negeri 1 Tilango, Gorontalo Regency can be explained by the management of school operational assistance (BOS) fund, while the remaining 72.3% is impacted by other variables which are not studied in this current research.